RATIONALITY IN MORAL PHILOSOPHY HUSAYN KASHIFI - Alimov Akbar (European Journal of Humanities and Educational Advancements, 2021)
This article philosophically and methodologically analyzes the characteristics of moral principles in the scientific heritage of Hussein Vaiz Koshifiy. The article also highlights the essence of the principle of rationality in the moral philosophy of Husayn Kashifi.